Antiangiogenic tyrosine kinase inhibitors in non-small-cell-lung cancer: lights and shadows - Gasparini, Giampietro (Translational Lung Cancer Research, 2012)
The MONET-1 prospective, multicenter randomized trial evaluating whether motesanib, a selective oral inhibitor of vascular endothelial growth factor (VEGF) receptors 1, 2 and 3; platelet-derived growth factor (PLGF) receptor and Kit, when combined with a standard carboplatin/paclitaxel cytotoxic schedule improves overall survival (OS) versus the same chemotherapy alone as first-line therapy for advanced non squamous non-small-cell-lung cancer reported by Scagliotti et al. (1) is well-conducted, evaluated and reported.